Croatia : Country Financial Accountability Assessment - World Bank (Washington, DC, 2012)
Croatia focuses much of its modernization efforts on meeting the requirements for accession to the European Union (EU), which include public financial management (PFM). In this context, the relevance of this Country Financial Accountability Assessment (CFAA) is evident. It assesses the legal framework, institutional capacity, and practices, for the core financial control processes, such as budgeting, treasury, and cash management, accounting, financial reporting, internal control and audit, as well as external audit, and parliamentary oversight. The basic approach of this CFAA has been to compare PFM practices in Croatia, with those promoted by relevant international standards, including also a specific set of indicators of fiduciary risk. The report concludes that the overall fiduciary risk is significant. Most of the weaknesses in the PFM arrangements revolve around inefficiencies in the existing financial accounting, and management systems. Moreover, a specific and serious deficiency identified in this report, is the lack of a sound internal control framework in the Ministry of Finance's (MOF) Public Debt Management Section. The CFAA offers a number of recommendations: a) the Minister of Finance should assign an Assistant Minister to develop, and implement a strategic vision for the future evolution, and rationalization of the financial systems; b) the MOF should commission an independent systems audit of the SAP - trademark of financial accounting and management information system - system; and, c) the MOF should establish an inter-ministerial steering committee to oversee the development of the SAP system. Further recommendations include issuing internal audits as referred to the organic Budget Act; initiating legislative changes to establish internal audits; appointing financial controllers; and, the State Audit Office should initiate the proposed legislative changes to the Act and State Audit.